Economic and political perspectives for water resources in the Middle East: a particular emphasis on Turkey and Syria-Iraq - Fisunoglu M. (Interdependency between agriculture and urbanization: Conflicts on sustainable use of soil and water, 2001)
The aim of this study is as follows: it is intended to analyze water resource conflict between Turkey and Syria-Iraq. The major rivers of the Middle East (The Nile, Euphrates and Tigris) and the secondary rivers such as Yarmouk, Jordan and Orontes are all transboundry rivers. The Tigris and The Euphrates have become a subject of conflict between Turkey and Iraq- Syria, and The Orontes between Turkey and Syria, in the recent years. Conflict has different perspectives; from economie to political. This paper is going to concentrate on economie and political consequences of transboundry water disputes between Turkey and Syria- Iraq.
Seminar: Interdependency between Agriculture and Urbanization: Conflicts on Sustainable Use of Soil and Water, 2000/04/02-06, Tunis (Tunisia)